ARTEMETER-LUMEFANTRINE THERAPEUTIC EFFICACY, SAFETY AND PLASMA LEVELS IN PATIENTS WITH UNCOMPLICATED FALCIPARUM MALARIA FROM THE COLOMBIAN PACIFIC REGIÓN - Alberto Tobón-Castaño (Asociación Colombiana de Infectología, 2018)
Introduction: In Colombia, the published studies for the treatment of uncomplicated Plasmodium falciparum malaria with Artemether-Lumefantrine are scarce. The aim of the study was to evaluate the therapeutic efficacy and safety profile of this combination. Methods: A clinical trial was performed in adults with uncomplicated P. falciparum malaria using the 28‑day World Health Organization validated protocol. Patients received supervised antimalarial treatment and the primary efficacy endpoint was the clinical and parasitological response. Safety was assessed through adverse events surveillance and plasmatic levels of antimalarial drugs were measured. Results: 88 patients were included. Adequate clinical and parasitological response rate of 100% on day 28 was achieved in 84 patients, diagnosed by thick blood smear examination. There were four parasitological therapeutic failures (5%) detected by polymerase chain reaction. Discusion: Therapeutic efficacy similar to previous studies was established with a slight increase in therapeutic failure. The serum levels of the antimalarials were adequate and the few cases of therapeutic failure were not related. Conclusion: Treatment of uncomplicated P. falciparum malaria with Artemeter-Lumefantrine was effective and safe in the study population. All patients reached adequate plasma concentrations of the drugs; therapeutic failures were not associated with low blood levels of the drug clinical trial.